Pengaruh Pemberian Pupuk Kalium dan Giberelin terhadap Pertumbuhan dan Produksi Tanaman Cabai (Capsicum annum L.) - Deviyanti, Vania Mulya; Kristanto, Budi Adi; Kusmiyati, Florentina (UNIVERSITAS LABUHANBATU, 2023)
The need for chili in Indonesia is always increasing every year, so it is necessary to take action to increase production by fertilization and using plant regulatory substances. This study aims to examine the effect of giving the best dose of potassium fertilizer and gibberellin concentration for the growth and production of chili plants. The research was conducted from May 2022 to August 2022 at the Screen House, Laboratory of Physiology and Plant Breeding, Laboratory of Ecology and Plant Production, Faculty of Animal Husbandry and Agriculture, Diponegoro University, Semarang. The research design used a 4 x 4 factorial design on the basis of Completely Randomized Design (CRD) with 3 replications. The first factor was the difference dose of K2O, K1: control (without K2O), K2: 60 kg/ha K3: 120 kg/ha dan K4: 180 kg/ha. The second factor was the difference concentration of gibberellin, G1: control (0 ppm), G2: 100 ppm G3: 125 ppm dan G4: 150 ppm. The data was analyzed using ANOVA (Analysis of Variance) and further test with Duncan Multiple Range Test (DMRT) at the level of five percent (5%). The results showed that the treatment of K2O fertilizer had a significant effect on the parameters of the plant height, the number of leaves and potassium up take of chili plant.Â Keywords: chili,gibberellin, K2O